2006
DOI: 10.1016/j.jfa.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of solution in terms of generalized eigenfunctions for a hyperbolic system with static boundary condition

Abstract: This paper studies a linear hyperbolic system with static boundary condition that was first studied in Neves et al. [J. Funct. Anal. 67(1986) 320-344]. It is shown that the spectrum of the system consists of zeros of a sine-type function and the generalized eigenfunctions of the system constitute a Riesz basis with parentheses for the root subspace. The state space thereby decomposes into topological direct sum of root subspace and another invariant subspace in which the associated semigroup is superstable: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Secondly, it is shown that the closed loop system has a sequence of generalized eigenfunctions, which form a Riesz basis for the state space, and hence the spectrum-determined growth condition holds. This generalizes the results proved in [11,12] where the matrix K (respectively the diagonal matrix M) has continuously differentiable (respectively continuous) coefficients and also those in [16] and the application in [37] where the coefficients are constants. Now let us outline the content of this paper.…”
Section: Hiii (Dissipativity)supporting
confidence: 86%
See 2 more Smart Citations
“…Secondly, it is shown that the closed loop system has a sequence of generalized eigenfunctions, which form a Riesz basis for the state space, and hence the spectrum-determined growth condition holds. This generalizes the results proved in [11,12] where the matrix K (respectively the diagonal matrix M) has continuously differentiable (respectively continuous) coefficients and also those in [16] and the application in [37] where the coefficients are constants. Now let us outline the content of this paper.…”
Section: Hiii (Dissipativity)supporting
confidence: 86%
“…Furthermore, the assumption H.III ensures the dissipativity of the system operator. Recently, the Riesz basis property has been investigated for the system (1.1), with a diagonal matrix M and dynamic as well as static boundary conditions [11,12]. As pointed out, the smoothness of the coefficients K i and M i, j has been used in the works cited above.…”
Section: Hiii (Dissipativity)mentioning
confidence: 99%
See 1 more Smart Citation
“…From Theorems and , it is easy to obtain that the multiplicities of the eigenvalues of scriptA are uniformly bounded. Therefore, by , we obtain that the system associated with scriptA satisfies the spectrum‐determined‐growth condition, that is, ω(scriptA)MathClass-rel=S(scriptA), where ω(scriptA)MathClass-rel=msubnormallimtMathClass-rel→MathClass-rel∞1tnormallnMathClass-rel∥escriptAtMathClass-rel∥ is the growth order of escriptAt and S(scriptA)MathClass-rel=normalsup{frakturRλMathClass-rel|λMathClass-rel∈σ(scriptA)} is the spectral bound of scriptA. The proof of Theorem is complete.…”
Section: Spectrum‐determined‐growth Condition (Proof Of Theorem 23)mentioning
confidence: 99%
“…New results on nonautonomous neutral equations with atomic difference operators in Banach spaces can be found in [12,Section 6]. It is shown in [23,24] that neutral equation with atomic difference operators can be studied as hyperbolic systems (see also [10] for new results on such systems).…”
mentioning
confidence: 99%